Inhibition of JAK2 and MDM2 to treat secondary acute myeloid leukemia evolving from myelofibrosis - Fuping Wang; Longxin Chen; Limeng Zhang; Siyu Du; Yingying Feng (Egyptian Journal of Medical Human Genetics)
Abstract Myelofibrosis (MF) is characterized by splenomegaly, extramedullary hematopoiesis, bone marrow fibrosis, anemia, constitutional symptoms, and risk of secondary acute myeloid leukemia (sAML). The prognosis for sAML is very poor, with a median survival of less than 6 months, largely due to its resistance to treatment. The main cause of death in MF patients is leukemic transformation. Leukemic transformation requires genetic mutations, such as the JAK2 V617F mutation, which is present in most sAML patients. Mutations in TP53 or the amplification of genes that negatively regulate p53 occur more frequently in sAML than in de novo acute myeloid leukemia (AML). Currently, the treatment of sAML poses a substantial challenge to the medical community. This review explored the potential of targeting JAK2 and MDM2 for the treatment of secondary AML caused by myelofibrosis. This review describes the research on sAML in relation to JAK2 and p53, outlines the interaction between JAK2, p53, mtP53, and MDM2, summarizes the effectiveness of JAK2 and MDM2 inhibitors, and advocates a combined approach using JAK2 and MDM2 inhibitors as a potential treatment strategy for sAML evolving from myelofibrosis. Inhibition of JAK2 and MDM2 may help improve the specificity and efficiency of sAML treatment and address drug resistance.